2011
DOI: 10.1007/s11357-011-9241-5
|View full text |Cite|
|
Sign up to set email alerts
|

Early dysfunction of functional connectivity in healthy elderly with subjective memory complaints

Abstract: It is still an open question whether subjective memory complaints (SMC) can actually be considered to be clinically relevant predictors for the development of an objective memory impairment and even dementia. There is growing evidence that suggests that SMC are associated with an increased risk of dementia and with the presence of biological correlates of early Alzheimer's disease. In this paper, in order to shed some light on this issue, we try to discern whether subjects with SMC showed a different profile o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 51 publications
0
20
0
1
Order By: Relevance
“…Unfortunately, data of such a control group were currently not available. Given that patients in the control group had subjective memory complaints, which is a risk factor for developing MCI and later AD, it may well be that DLB patients deviated more from controls in their clinical profile than the AD group. The use of medication acting on the CNS was significantly higher in the DLB group, which may have affected resulted, although in a previous work, no medication effects on functional connectivity patterns were found, for example, for antiepileptic drugs .…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, data of such a control group were currently not available. Given that patients in the control group had subjective memory complaints, which is a risk factor for developing MCI and later AD, it may well be that DLB patients deviated more from controls in their clinical profile than the AD group. The use of medication acting on the CNS was significantly higher in the DLB group, which may have affected resulted, although in a previous work, no medication effects on functional connectivity patterns were found, for example, for antiepileptic drugs .…”
Section: Discussionmentioning
confidence: 99%
“…This latter point is important because it suggests that hypersynchronization reflects a pathological state within the neuronal networks. By contrast, individuals with subjective memory complaints (but no evidence of object memory loss) actually underexpress a network that supports recognition memory (Bajo et al, 2012b). Thus, there seems to be a dynamic change in brain function over the spectrum of normal aging through subjective memory complaints to MCI to dementia.…”
Section: Functional Organization and White Matter Integrity In MCImentioning
confidence: 93%
“…Long-range synchronization between signals originating in relatively distant neuronal populations is one potential mechanism for communication and integration of information in the brain (Varela et al 2001; Fries 2005; Engel et al 2001). Studies of elderly individuals with mild cognitive impairment have shown that alterations in functional connectivity precede the development of clinical dementia and are related to the time to develop dementia (Bajo et al 2011; Bajo et al 2010). The purpose of this pilot study is to analyze MEG data from a group of patients with HIV disease and risk-group appropriate controls to determine the extent to which measures of functional connectivity could serve as a useful CNS biomarker of HIV infection.…”
Section: Introductionmentioning
confidence: 99%